Prevalence and Determining of Alcohol use disorder among Students at the National University of Laos - Latsamy Oulay; Vanmaika Vang; Souksamone Thongmixay; Vathsana Somphet; Vanphanom Sychareun (International Journal of Public Health Asia Pacific, 2026)
Background: Alcohol consumption poses significant health risks, particularly among adolescents and young adults. In the Lao People’s Democratic Republic (Lao PDR), alcohol use is a growing public health concern, with the highest per capita alcohol consumption in Southeast Asia. Excessive drinking, especially alcohol use disorder (AUD) contributes substantially to non-communicable diseases and risky behaviours among young people. Objectives: This study aimed to assess the prevalence of alcohol use disorder and identify associated risk and protective factors among university students in Lao PDR. Methods: A cross-sectional analytical study was conducted among 744 undergraduate students at the National University of Laos (NUOL) between June and October 2023. Participants completed a structured self-administered questionnaire on sociodemographic characteristics, drinking behaviours, and psychosocial variables. Data were analysed using STATA version 16.1, with descriptive statistics and multivariate logistic regression. Results: Overall, 57% were male, most were aged 18-19 years and enrolled in natural science programs. The prevalence of alcohol use disorder was 45.4%. Key risk factors included having a mother with tertiary education (AOR=2.95; 95%CI:1.80-4.82), receiving higher monthly pocket money (AOR=1.75; 95%CI:1.21-2.55), and drinking with peers or alone (AOR=1.51; 95%CI:1.04-2.19). Protective factors included being a second-year student, enrolled in social science programs, first intoxication (≥16 years), higher academic performance, strong social support, abstaining from sexual activity, and non-smoking status. Conclusion: Alcohol use disorder is common among university students in Laos, particularly young males. The findings highlight the influence of family background, peer behaviour, academic factors and lifestyle choices. Tailored health promotion strategies and campus-based interventions are urgently needed to reduce harmful alcohol use and improve student well-being.